PENGARUH KESEJAHTERAAN KARYAWAN, LINGKUNGAN KERJA FISIK, FASILITAS KERJA, BEBAN KERJA DAN BUDAYA ORGANISASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA CV. SARANA AIR TRIOLA - Ericka Sesa; Risma Amelia, Talia Srimuliani, Tri Apriyono (CV. ADIBA AISHA AMIRA, 2024)
Organizations need productive human resources (HR) to achieve goals. One of the factors that influence employee productivity are various aspects such as welfare, physical work environment, work facilities, workload, and organizational culture. This research aims to analyze the influence of these factors on employee work productivity at CV. Sarana Air Triola, a bottled drinking water (AMDK) industrial company. This research uses a quantitative approach with descriptive and explanatory methods, involving 19 employees as research samples. Data analysis was carried out using multiple linear regression using SPSS version 26 software. The research results showed that simultaneously, all independent factors (employee welfare, physical work environment, work facilities, workload and organizational culture) had a significant effect on employee work productivity with a significant value. 0,000. Partially, workload and work facilities have a significant influence with significance values of 0.000 and 0.010, while other variables show a weaker influence. The R Square test results show that 77.3% of the variation in employee productivity can be explained by this model, with the contribution of these variables. This research provides important insights for companies in increasing work productivity through managing factors that influence employee performance